Clinical efficacy and predictive factors of photodynamic therapy combined with recombinant mussel mucin repair dressing in treating post-inflammatory hyperpigmentation - Nie, Jianjun; Hou, Zengmiao; Zhou, Peimei; Zhang, Ya; Lu, Yonghong (Frontiers in Medicine, 2026)
ObjectiveTo evaluate the efficacy and safety of photodynamic therapy (PDT) combined with recombinant mussel mucin repair dressing in treating post-inflammatory hyperpigmentation (PIH), and to assess its impact on patient quality of life.MethodsIn a prospective, controlled, non-randomized clinical study, we enrolled 310 patients (Fitzpatrick III–IV) with epidermal or dermal PIH. Patients underwent PDT by wavelength and energy protocol, followed by immediate application of recombinant mussel mucin repair dressing. Pigmentation area, melanin density, adverse events, recurrence, and quality of life were assessed over 14 months.ResultsThe combined therapy achieved significantly greater pigment clearance at 4 weeks (42.3 vs. 25.6% in controls, p < 0.001), larger melanin density reduction (31.5 vs. 17.2%, p = 0.002), fewer phototoxic reactions (6.5 vs. 14.1%, p = 0.021), and lower recurrence at 14 months (13.2 vs. 27.8%, p = 0.011). Patient-reported quality of life markedly improved (median DLQI score from 35 to 68, p < 0.001).ConclusionPDT combined with recombinant mussel mucin repair dressing provides superior pigment clearance, reduced recurrence, improved safety, and enhanced quality of life compared with standard therapy. This multimodal approach offers a promising option for PIH management in darker skin types.